Kawasaki Disease in Children Older Than 10 Years: A Clinical Experience From Northwest India - Jindal, Ankur Kumar; Pilania, Rakesh Kumar; Guleria, Sandesh; Vignesh, Pandiarajan; Suri, Deepti; Gupta, Anju; Singhal, Manphool; Rawat, Amit; Singh, Surjit (Frontiers in Pediatrics, 2020)
Background: Kawasaki disease (KD) is predominantly seen in young children (<5 years). Diagnosis of KD is often delayed in older children and adolescents, leading to a higher risk of coronary artery abnormalities (CAAs). There is a paucity of literature on KD in older children. Methods: Data were collated from a review of records of patients diagnosed with KD who were aged ≥10 years at the time of diagnosis, during the period from January 1994 to June 2019. Results: Eight hundred and sixty five patients were diagnosed with KD during this period. Of these, 46 (5.3%; 26 boys and 20 girls) were aged 10 years or older at the time of diagnosis. The median age at diagnosis was 11 years (range of 10–30 years). The median interval between the of fever and the diagnosis of KD was 12 days (range of 4–30 days). Eight patients (17.4%) presented with hypotensive shock. Coronary artery abnormalities (CAAs) were seen in six patients (13.04%), and three patients had myocarditis. Patients with CAAs were found to have significantly higher median platelet counts and higher median C-reactive protein levels. First-line treatment included intravenous immunoglobulin. Adjunctive therapy was given in five patients (infliximab in four patients and steroids in one patient). The median time between the onset of fever and the administration of IVIg was 13.5 days (range of 6–2). The total duration of follow up is 2,014.5 patient-months. Conclusion: Diagnosis of KD in children older than 10 years is usually delayed, and these patients are thus at a higher risk of CAAs.